2022
DOI: 10.1007/s00432-022-03953-y
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair deficiency, chemotherapy and survival for resectable gastric cancer: an observational study from the German staR cohort and a meta-analysis

Abstract: Purpose In a post hoc analysis of the MAGIC trial, patients with curatively resected gastric cancer (GC) and mismatch repair (MMR) deficiency (MMRd) had better median overall survival (OS) when treated with surgery alone but worse median OS when treated with additional chemotherapy. Further data are required to corroborate these findings. Methods Between April 2013 and December 2018, 458 patients with curatively resected GC, including cancers of the esopha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This was initiated by analyzing resected specimens of the patients participating in the MAGIC trial, which was the first trial demonstrating the advantages of pre/perioperative CTx including epirubicin, cisplatin and 5FU compared to treatment with surgery alone in 2006 and since then has been the standard of care in Western countries for years (Cunningham et al 2006;Lordick et al 2022). The results regarding the prognostic relevance of MSI-H in this trial and in subsequent reports indicated that pre-/ perioperative CTx would not be beneficial to patients with MSI and may even harm them compared to patients treated with surgery alone (Smyth et al 2017;Pietrantonio et al 2019;Stolze et al 2022). No sex-specific data of MSI-H patients are available, but owing to the relatively strong dominance of males in the study, the majority of MSI-H patients may be men (Cunningham et al 2006;Smyth et al 2017).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This was initiated by analyzing resected specimens of the patients participating in the MAGIC trial, which was the first trial demonstrating the advantages of pre/perioperative CTx including epirubicin, cisplatin and 5FU compared to treatment with surgery alone in 2006 and since then has been the standard of care in Western countries for years (Cunningham et al 2006;Lordick et al 2022). The results regarding the prognostic relevance of MSI-H in this trial and in subsequent reports indicated that pre-/ perioperative CTx would not be beneficial to patients with MSI and may even harm them compared to patients treated with surgery alone (Smyth et al 2017;Pietrantonio et al 2019;Stolze et al 2022). No sex-specific data of MSI-H patients are available, but owing to the relatively strong dominance of males in the study, the majority of MSI-H patients may be men (Cunningham et al 2006;Smyth et al 2017).…”
Section: Discussionmentioning
confidence: 80%
“…No sex-specific data of MSI-H patients are available, but owing to the relatively strong dominance of males in the study, the majority of MSI-H patients may be men (Cunningham et al 2006;Smyth et al 2017). In addition, the analysis of only resected specimens after preoperative CTx, which necessarily leads to the exclusion of responding patients with minimal or no residual tumor cells in the resected specimen, may introduce some bias and represent a limitation for generalization (Smyth et al 2017, Stolze, Franke et al 2022. Furthermore, several studies have not found a negative prognostic effect of MSI-H in the neoadjuvant chemotherapeutic setting (Haag et al 2019;Hashimoto et al 2019;Kohlruss et al 2019;Quaas et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was the number of cases of PTSD among TBI patients. The odds ratio was calculated as previously described [ 38 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The authors reported that dMMR/MSI-H was associated with better OS and disease-free survival (DFS) at five years. However, patients with gastric cancer with dMMR/MSI-H had worse outcomes when treated with perioperative chemotherapy [62]. Furthermore, neoadjuvant chemotherapy led to an increased incidence of complications related to surgery [63].…”
Section: Neoadjuvant Immunotherapy For Patients With Dmmr/msi-h Gastr...mentioning
confidence: 99%